Current Application Status of Photoelectric Pre-discarded Technology in Waste Rock Recovery Process - Zhiming LU; Ruoyu YAO; Xiong TONG; Qiang SONG (Kuangchan zonghe liyong)
Our country boasts abundant mineral resources, but they are of a low grade, with a fine distribution and complex composition. With the increase of the consumption of mineral resources, the amount of waste rock generated is also increasing. The large accumulation of waste rock not only occupies valuable land resources but also causes environmental pollution. Therefore, the recycling and utilization of waste rock is an effective way to improve resource efficiency, conserve mineral resources, and protect the ecological environment. Extracting valuable components from waste rock is key to maximizing its utilization, and pre-discarded is an important basis for the efficient utilization of waste rocks. This paper introduces the application of photoelectric beneficiation technology in pre-discarded of waste rock, compares and analyzes the advantages and disadvantages of different photoelectric beneficiation technologies such as XRT, image color separation, and XRF, and looks forward to the future development of photoelectric beneficiation technology in the field of pre-disposal.